2018
DOI: 10.1186/s12889-018-5244-9
|View full text |Cite
|
Sign up to set email alerts
|

Community perception regarding childhood vaccinations and its implications for effectiveness: a qualitative study in rural Burkina Faso

Abstract: BackgroundVaccination has contributed to major reductions in global morbidity and mortality, but there remain significant coverage gaps. Better knowledge on the interplay between population and health systems regarding provision of vaccination information and regarding health staff organization during the immunization sessions appears to be important for improvements of vaccination effectiveness.MethodsThe study was conducted in the Nouna Health and Demographic Surveillance System (HDSS) area, rural Burkina Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(80 citation statements)
references
References 35 publications
2
69
0
5
Order By: Relevance
“…It was revealed that children from large families have low vaccine uptakes, considering the burden of other children at home in taking up immunization services [11,13,25,46,50]. Migration was also cited as a hindrance to childhood immunization coverage [30,35,44,48]. Feeling ashamed of poverty-associated reasons was reported as barrier.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was revealed that children from large families have low vaccine uptakes, considering the burden of other children at home in taking up immunization services [11,13,25,46,50]. Migration was also cited as a hindrance to childhood immunization coverage [30,35,44,48]. Feeling ashamed of poverty-associated reasons was reported as barrier.…”
Section: Resultsmentioning
confidence: 99%
“…Health workers were reported to cover long distances on outreach services due to inadequate health centers [11,13,15,43]. The restricted vaccine opening policy (Use of multi-dose vails and the limited time for their use) was noted as a barrier specifically for the BCG vaccine [18,30,43]. It was also cited that reminders were not sent on time about routine immunization or outreach days [48]…”
Section: Providers Barriersmentioning
confidence: 99%
“…Forty-eight articles met all inclusion criteria for this study; 28 articles were excluded for various reasons. [See supplementary materials 3] Nine articles employed second-hand data analysis [7,12,18,27,37,40,41,47,42]; thirty-six used crosssectional design [1][2][3]11,[13][14][15][16][17]19,[21][22][23][24][25][26][28][29][30][31][32][33][34][35][36][38][39]42,[45][46][48][49][50][51]53,54] and three used case-control study [20,[43][44]. All described studies were conducted on Africa populations (103,655 adults and 76,327 children).…”
Section: Resultsmentioning
confidence: 99%
“…One critically examined barriers speci c to vaccination doses at birth 0 -1day [18] in the Gambia. Thirty articles reported national immunization coverage [1][2]7,[11][12][13][14][15][16][20][21][22][23][24][25][28][29]32,[34][35][38][39][40][43][44][45][46]49,50,[52][53][54], eighteen did not [3,[17][18][19]22,24,[26][27][30][31]33,[36][37][41][42]47,48,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation